Adaptive Extended Kalman Prediction-Based SDN-FANET Segmented Hybrid Routing Scheme - Ke Sun; Mingyong Liu; Chuan Yin; Qian Wang (Sensors)
Recently, with the advantages of easy deployment, flexibility, diverse functions, and low cost, flying ad hoc network (FANET) has captured great attention for its huge potential in military and civilian applications, whereas the high-speed movement and limited node energy of unmanned aerial vehicles (UAVs) leads to high dynamic topology and high packet loss rate in FANET. Thus, we introduce the software-defined networking (SDN) architecture into FANET and investigate routing scheme in an SDN-FANET to harvest the advantages of SDN centralized control. Firstly, a FANET segmented routing scheme based on the hybrid SDN architecture is proposed, where inter-segment conducts energy-balanced routing and intra-segment adopts three-dimensional (3D) greedy perimeter stateless routing (GPSR). Specifically, we design the specific process of message interaction between SDN controller and UAV nodes to ensure the execution of the inter-segment routing based on energy balance. Further, to reduce the packet loss rate in high-speed motion scenes, an adaptive extended Kalman prediction algorithm is also proposed to track and predict the 3D movement of UAVs. Simulations verify the effectiveness of the proposed routing scheme in terms of end-to-end delay and packet delivery ratio.